A house divided: religion and the American imperial debate, 1890-1902 - Hamer, Michael D. (Kansas State University, 2016)
American society has been heavily influenced by religion, since before the United States existed as a nation. It has provided a sense of providential guidance and protection that has shaped or influenced internal politics and foreign policy alike. How were attitudes toward expansion and imperialism affected by religion throughout American history? Was the resultant ideology consistent? If not, what changed to cause a shift? The purpose of this thesis is to explore those questions. Using a wide breadth of material including primary and secondary sources, this thesis demonstrates that society was heavily influenced by religious rhetoric, whether spoken from the pulpit or in print. It further demonstrates how political leaders and religious leaders utilized rhetoric of divine causation and justification in addition to more tangible factors such as economics or security for expansionist thought. Significantly, concepts of racism were justified or reviled in religious terms. Ironically, opposing views on these topics both chose to use religion as their weapon to prove their points. Culminating at the time of the Spanish-American War of 1898, and the follow-on Philippine-American War, the imperial debate was heavily influenced by religion and was a milestone in transforming American national policy and thought.
Keywords: Religion; Imperialism; Cuba; Philippines; William Jennings Bryan; William McKinley